2015
DOI: 10.1103/physreva.92.062113
|View full text |Cite
|
Sign up to set email alerts
|

Continuous decomposition of quantum measurements via Hamiltonian feedback

Abstract: We characterize the set of generalized quantum measurements that can be decomposed into a continuous measurement process using a stream of probe qubits and a tunable interaction Hamiltonian. Each probe in the stream interacts weakly with the target quantum system, then is measured projectively in a standard basis. This measurement result is used in a closed feedback loop to tune the interaction Hamiltonian for the next probe. The resulting evolution is a stochastic process with the structure of a one-dimension… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Ahn et al [12] investigated using continuous-time quantum measurements for this purpose, thus pioneering a fruitful line of research [13][14][15][16][17][18][19][20][21]. Feedback control additionally allows one to view weak measurements as building blocks for constructing other generalized measurements, as explored by Brun and collaborators [22][23][24][25]. Continuous weak measurements have also been pressed into service for parameter and state estimation [26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Ahn et al [12] investigated using continuous-time quantum measurements for this purpose, thus pioneering a fruitful line of research [13][14][15][16][17][18][19][20][21]. Feedback control additionally allows one to view weak measurements as building blocks for constructing other generalized measurements, as explored by Brun and collaborators [22][23][24][25]. Continuous weak measurements have also been pressed into service for parameter and state estimation [26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…A feature worth pointing out in continuous measurements is the use of an adaptive procedure that updates the current status for the next step of measurement. This feedback technique has both experimental advantage for practical designs [14][15][16][17][18] and theoretical importance for the ability to realize more general classes of quantum measurements [19][20][21][22]. In quantum optics, for example, the phase measurement of a single mode can be improved by feedback loops during the measurement process [14,15], and it was also used in the preparation and stabilization of photon number states [16].…”
Section: Introductionmentioning
confidence: 99%
“…It is also well-known that any generalized measurement for a system is equivalent to letting the system interact with an ancilla followed by a projective measurement on the ancilla. In [21,22], it is shown that what classes of generalized measurements can be achieved by tuning the probe state or the interaction Hamiltonian during the continuous measurement process.…”
Section: Introductionmentioning
confidence: 99%
“…A more powerful model [8] again characterizes the set of generalized measurements that can be decomposed into a sequence of weak measurements based on interactions between a stream of qubit probes and the system, but now the interaction Hamiltonian between them can itself be varied based on the feedback. The work in [8] assumes that the interaction Hamiltonian is a linear combination of some fixed set of Hamiltonian terms. The achievable measurements in this model have measurement operators from a finite dimensional Jordan algebra within the span of the Hamiltonian terms.…”
Section: Introductionmentioning
confidence: 99%